Informational rents and the excessive entry theorem: The case of hidden action - Marco De Pinto; Laszlo Goerke; Alberto Palermo (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2023)
Entry in a homogeneous Cournot-oligopoly is excessive if there is business stealing. This prediction assumes that production costs reduce profits and welfare equally. However, this need not be the case. If there is asymmetric information, suppliers or employees can utilize their superior knowledge to extract informational rents. Rent payments reduce profits and deter entry, but affect neither the optimal number of firms nor welfare directly. Therefore, entry becomes insufficient if informational rents are large enough. In the context of a moral hazard model, we show that insufficient entry occurs if entry costs are sufficiently high. Such costs lower the number of firms and, thereby, raise informational rents.
Keywords: D43; D82; L51; 330; Oligopoly; excessive entry; informational rents; moral hazard